Production technologies in stochastic continuous time models - Wälde, Klaus 1966- (CESifo working papers, 2009)
Properties of dynamic stochastic general equilibrium models can be revealed by either using numerical solutions or qualitative analysis. Very precise and intuition-building results are obtained by working with models which provide closed-form solutions. Closed-form solutions are known for a large class of models some of which, however, have some undesirable features. This paper offers closed-form solutions for models which are just as tractable but do not suffer from these shortcomings. -- dynamic stochastic general equilibrium models ; closed-form solution ; continuous time ; jump diffusion